Isolation and characterization of Hexavalent chromium reducing proteus mirabilis isolated from the water of Buriganga River - Aktar, Most. Nasrin (BRAC University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.